Private Benefits of Control, Ownership, and the Cross‐listing Decision - DOIDGE, CRAIG; KAROLYI, G. ANDREW; LINS, KARL V.; MILLER, DARIUS P.; STULZ, RENÉ M. (Journal of Finance, 2009)
ABSTRACT This paper investigates how a foreign firm's decision to cross‐list on a U.S. stock exchange is related to the consumption of private benefits of control by its controlling shareholders. Theory has proposed that when private benefits are high, controlling shareholders are less likely to choose to cross‐list in the United States because of constraints on the consumption of private benefits resulting from such listings. Using several proxies for private benefits related to the control and cash flow ownership rights of controlling shareholders, we find support for this hypothesis with a sample of more than 4,000 firms from 31 countries.